2003
DOI: 10.1149/1.1577336
|View full text |Cite
|
Sign up to set email alerts
|

Single Bath, Pulsed Electrodeposition of Copper-Tin Alloy Negative Electrodes for Lithium-ion Batteries

Abstract: Single-bath, pulsed electrodeposition of Cu-Sn alloy films was performed in a bath containing Lucent Technology’s SnTech plating solution and copper sulfate. Films with varying Cu-Sn stoichiometries were deposited. Deposited films were between ∼3 and 6 μm thick. These films were used as working electrodes in Li/Cu-Sn electrochemical cells to test their suitability as negative electrodes for Li-ion cells. As the Cu content in the film is increased, specific capacity is sacrificed for capacity retention. Films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 15 publications
3
79
0
3
Order By: Relevance
“…This is a common method to apply a metallic protective fi lm on industrial scale but it can also be applied at lab-scale for the production of various battery layers. It has been demonstrated that, for example, Cu 2 Sb, [ 193 ] V 2 O 5 , [ 194 ] MnO 2 , [ 195 ] MoS 2 [ 176 , 177 ] and metallic anodes like Bi, [ 196 ] Sn [ 197 ] and Cu-Sn alloys [ 198 ] can be deposited using electrodeposition.…”
Section: Physical Vapor Depositionmentioning
confidence: 99%
“…This is a common method to apply a metallic protective fi lm on industrial scale but it can also be applied at lab-scale for the production of various battery layers. It has been demonstrated that, for example, Cu 2 Sb, [ 193 ] V 2 O 5 , [ 194 ] MnO 2 , [ 195 ] MoS 2 [ 176 , 177 ] and metallic anodes like Bi, [ 196 ] Sn [ 197 ] and Cu-Sn alloys [ 198 ] can be deposited using electrodeposition.…”
Section: Physical Vapor Depositionmentioning
confidence: 99%
“…To easily and simply improve the cyclability of the Sn film electrode, we have selected a constant current pulse electrodeposition method because it is easy to accurately control the element content of the alloy [10] and obtain uniform and fine crystal grains [11]. Moreover, due to its high surface area and short ion diffusion length, it is well known that an electrode would show a good kinetic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the cycling performance of Sn anodes, different strategies have been implemented to prevent the adverse effects of large volume changes. Among them, one strategy is to develop Sn-based intermetallic compounds such as Cu 6 Sn 5 (10)(11)(12), CoSn 3 (13) and Ni 3 Sn 4 (14)(15)(16), in which inactive elements compensate for the expansion/ contraction of Sn. The intermetallic anodes have a lower specific capacity than pure Sn, but their capacity retention is significantly higher.…”
Section: Introductionmentioning
confidence: 99%